Theoretical support for staff satisfaction in higher education institutions: a conceptual framework - Mohamad Hazeem Mohmad Sidik,; Mohd Rashid Ab Hamid,; Abdullah Ibrahim,; Zarina Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this paper, the theoretical foundation for staff satisfaction in Higher Education Institutions (HEIs) conceptual framework is discussed. Several constructs are identified based on the evidence from previous studies. This framework has been developed based on the relationships of these constructs and staff satisfaction as evidence from past studies that have been supported by three theories in the field of psychology. Seven salient constructs of the framework are: (1) leadership, (2) staff involvement, (3) workload, (4) self-development, (5) working environment, (6) communication, and (7) job satisfaction. All constructs have been found to be inter-related and contributed to overall satisfaction of HEI members of staff in the organisations which could possibly enhance their intention to stay or to leave their respective workplace. The framework is potentially useful for future testing and validation in the context of higher education setting.